Peningkatan Keterampilan Membaca Permulaan menggunakan Pop-Up Book Berbasis Augmented Reality pada Siswa Sekolah Dasar Kelas 1 - Munajah, Robiatul; Nisphia, Jasmin; Faruq, Umar Al; Arifitama, Budi; Budiana , Kiki; Kilawati , Andi (Journal of Education Reseach and Evaluation, 2025)
Elementary school students' early reading skills are still low, resulting in delays in understanding learning materials. The lack of innovative and interactive learning media causes students to be less motivated in developing early literacy skills. This study aims to analyze the effectiveness of augmented reality-based pop-up book media in improving students' early reading skills by emphasizing analysis, evaluation, and application skills. The type of research used is an experiment with a single-group pretest-posttest design. The research subjects involved 35 students aged 6–7 years as trial subjects. Data were collected through a test of early reading skills using pretest and posttest instruments. Data analysis was carried out using a t-test to determine the average difference before and after treatment. The results of the study showed a significant increase in students' early reading skills after using augmented reality-based pop-up book media, which proves that this media is able to support the learning process more effectively and enjoyably. The conclusion of this study confirms that augmented reality-based pop-up book media is effective in improving students' early reading skills, while addressing the problem of low basic literacy. The implications of this research indicate that the use of interactive technology can be an important strategy for teachers to enrich early literacy learning media to make it more interesting, contextual, and appropriate to the needs of the digital generation.